Estudo de propriedades biofísicas de vesículas unilamelares gigantes como modelo para entrega intracelular de materiais: eletroporação e fusão de membranas - Lira, Rafael Bezerra de [UNIFESP] (2016)
Biological membranes are the structures that define the boundaries of cells, acting as a selective barrier, regulating the intra and extracellular transport. Many biological substances have their target in the cell?s interior, but are not able to cross the membrane to reach them. Therefore, many methods for the intracellular delivery of materials have been developed; among them, electroporation and fusogenic liposomes. During electroporation, one or more intense electrical pulses are applied and the membrane becomes transiently permeable, allowing the entry of the substances into the cell. The method is efficient but has high toxicity. The fusion between liposomes and cells results in the delivery of the liposome-encapsulated substance, but the underlying mechanisms are not well known and the efficiency is limited. Biomimetic models are generally employed to mimic real systems in a controlled way. One of the most common biomimetic system are the giant unilamellar vesicles (GUVs). In this thesis, we use GUVs with mixed the zwitterionic (PC) and anionic (PG) lipids to study the processes of electroporation and fusion with fusogenic liposomes, and both processes are studied by a series of microscopy-based techniques. Electroformed pores in electrically neutral GUVs are transient, with a pore lifetime in the order of a few milliseconds. In contrast, electroformed pores in some negatively charged GUVs open indefinitely, leading to a total vesicle collapse, in a process termed bursting. The results presented here show that the bursting fraction depends on the fraction of PG in the membrane, lipid insaturation (lipids with insaturation in one or both hydrophobic tails) e certain additives in the medium, especially Ca+2. Bursting propensity is related to the reduction n pore edge tension (?), from 57,9±26,1 e 53,7±11,5 pN in neutral POPC and DOPE membranes, respectively, to values lower than 20 pN in membranes containing PG ? 20 mol%. Such a reduction also depends on the presence of médium additives, and the ? values are higher for vesicles in the presence of Ca+2 compared to Na+, but only in the presence of PG ? 20 mol%. Destabilization propensity is, therefore, a result of a reduction in ?. Formed pores in charged membranes have a composition similar to that in intact membranes. Reminiscent pores after GUV electroporation have a higher permeability to macromolecules. Negative membranes also display differences in other membrane properties compared to neutral ones, such as reduction in lipid mobility, increase in membrane order and spontaneous curvature. The fusion of GUVs with different fractions of PG in PC membranes, with fusogenic liposomes, was studied in a new LUV-GUV fusogenic system, in which fusion was observed in real time and its effects directly observed and quantified under the microscope. In this system, many fusion intermediates (adhesion, hemifusion and full-fusion) can be detected and the morphological transformations directly observed. Förster resonance energy transfer (FRET) assays allow to measure the amount of lipids transferred from the LUVs to the GUVs, and show that the transition hemifusion6 full fusion occurs in the range of 10-20 mol% PG. At low PG mol fractions (? 10 mol%), the interaction leads mainly to adhesion and hemifusion and increases membrane tension, whereas at high PG mol fractions (? 20 mol%), the interaction results in full fusion, leading to GUV increase in area. The construction of a FRET calibration curve allows the determination of the final membrane composition after fusion in every GUV. During hemifusion, the amount of cationic lipids transferred fro LUVs is < 5 mol%, whereas upon full fusion, the final GUV composition contains up to 20 mol% DOTAP. In every case, fusion occurs by a charge neutralization mechanism. The results presented here (i) clarifies the responsible mechanisms of bursting of negatively charged GUVs, (ii) define the membrane charge determinants of fusion in a system of membranes with opposite charges and, (iii) show that many properties of electrically membranes are distinct from their neutral counterparts. We believe that the findings presented here may help on the development of better delivery systems, with better efficiency and lower side effects.